2001
DOI: 10.1016/s0022-5347(05)66351-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Transperineal Ultrasound Guided Template Biopsy of the Prostate in Patients at High Risk

Abstract: Systematic transperineal template biopsy of the prostate is a safe and precise repeat biopsy technique in patients who remain at high risk for adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 19 publications
3
24
1
1
Order By: Relevance
“…In the DREϩ first biopsy group, the carcinoma core rate in the posterior region of the prostate was significantly higher than in the anterior region. Of 273 carcinoma-positive biopsies, 211 (77%) were in the posterior region, suggesting that palpable carcinomas are distributed more often in the posterior region compared with the anterior region, a finding that is consistent with the result reported by Chen et al 12 However, in the repeat biopsy group, the carcinoma core rate in the posterior region was found to be significantly lower than in the anterior region, and 60% of the carcinoma-positive biopsies (34 of 57 biopsies) were taken from the anterior region, a finding that is largely consistent with the results reported by Igel et al 13 These results suggested that a segment of tumors occurring in the anterior region (mostly the TABLE 4 No transition zone) had been missed by previous transrectal sextant biopsies, although many of the tumors occurring in the posterior region (mostly the peripheral zone) had been detected. We demonstrated that carcinoma-positive biopsy cores are distributed equally throughout the entire prostate in patients with normal DRE findings and no previous prostate biopsy, which is quite different from the result reported by Epstein et al 11 Emiliozzi et al reported that transperineal biopsy missed fewer tumors than transrectal biopsy, and that it was superior to transrectal biopsy for the detection of early prostate carcinoma.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the DREϩ first biopsy group, the carcinoma core rate in the posterior region of the prostate was significantly higher than in the anterior region. Of 273 carcinoma-positive biopsies, 211 (77%) were in the posterior region, suggesting that palpable carcinomas are distributed more often in the posterior region compared with the anterior region, a finding that is consistent with the result reported by Chen et al 12 However, in the repeat biopsy group, the carcinoma core rate in the posterior region was found to be significantly lower than in the anterior region, and 60% of the carcinoma-positive biopsies (34 of 57 biopsies) were taken from the anterior region, a finding that is largely consistent with the results reported by Igel et al 13 These results suggested that a segment of tumors occurring in the anterior region (mostly the TABLE 4 No transition zone) had been missed by previous transrectal sextant biopsies, although many of the tumors occurring in the posterior region (mostly the peripheral zone) had been detected. We demonstrated that carcinoma-positive biopsy cores are distributed equally throughout the entire prostate in patients with normal DRE findings and no previous prostate biopsy, which is quite different from the result reported by Epstein et al 11 Emiliozzi et al reported that transperineal biopsy missed fewer tumors than transrectal biopsy, and that it was superior to transrectal biopsy for the detection of early prostate carcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, Igel et al used the transperineal template technique and reported that prostate carcinoma was identified in the transition zone area in 76% of patients (29 of 38 patients) who had previously undergone transrectal prostate biopsies and had negative results. 13 These results appear to be inconsistent, but we believe we are able to offer an explanation for the apparent discrepancy between them. In the DREϩ first biopsy group, the carcinoma core rate in the posterior region of the prostate was significantly higher than in the anterior region.…”
Section: Discussionmentioning
confidence: 64%
“…3 When compared to TR biopsy, studies on extended transperineal (TP) biopsy have been relatively limited and there has been no consensus on standard extended TP biopsy protocol. [4][5][6][7][8][9][10][11][12][13] The lack of standardization at the moment is related to both TP and TR approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The unifying theme of extended biopsies is one of maximizing cores taken from the lateral peripheral zone, the most common site of CaP. Extended, saturation, and transperineal biopsy templates have been studied and CaP detection rates range from 29-43% [18][19][20] . Regardless of the approach to biopsy, there remains a majority of patients at risk for CaP with a negative biopsy.…”
Section: Resultsmentioning
confidence: 99%